Organizational Structure and Expected Output at Nuclear Power Plants - Rothwell, Geoffrey (The Review of Economics and Statistics, 1996)
This paper examines the relationship between organizational structure and operation and outage durations at nuclear power plants in the United States. It empirically examines Aoki's (1990) proposition that (1) hierarchical control increases productivity in situations that are very stable or very uncertain and (2) horizontal coordination increases productivity in intermediate situations. It describes a model of continuous production in which management chooses an organizational structure that minimizes the ratio of the hazard rates for operation and outage. And proposes an index of hierarchy based on measures of plant-level organization. Parameter estimates support the proposition that less hierarchy is associated with higher productivity through longer periods of operation. Copyright 1996 by MIT Press.